Synthesis and Characterization of Sodium Diphenylcarbamodithioate Ligand [L] and its Cobalt, Nickel, and Copper Complexes - Alsalihi, Eman I.; Al-Fahdawi, Aeed S.; Meena, Bashdar I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
A correlation of the infrared spectra of thiocarbonyl derivatives based on the literature data has been carried out. Assignments have also been made in some new systems. Sodium Diphenylcarbamodithioate ligand and its monomeric complexes were synthesized at room temperature and stirring condition. The ligand and its complexes of the general formula [M(L)2] (where M= Co+2, Ni+2 and Cu+2) were characterized by spectroscopic methods (IR and ultraviolet-visible), elemental analysis (C.H.N. and S) metal content, magnetic susceptibility measurement, and biological activity (an antibacterial activity of the complex was studied by agar disc diffusion method and minimum inhibitory concentration strain against Staphylococcus aureus and Bacillus subtilis). The complex exhibited significant activities against S. aureus and B. subtilis, thin-layer chromatography, mass spectrometry, X-ray powder diffraction, and molar conductance. Our study revealed the formation of four-coordinate square planar complexes around Coп, Niп, and Cuп metal ions.